2006
DOI: 10.1200/jco.2005.03.3472
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Survival in African American and White American Patients With Breast Cancer: Ethnicity Compared With Socioeconomic Status

Abstract: Our pooled analysis demonstrated that African American ethnicity is a significant and independent predictor of poor outcome from breast cancer, even after accounting for socioeconomic status by conventional measures. These findings support the need for further investigation of the biologic, genetic, and sociocultural factors that may influence survival in African American patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
252
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(265 citation statements)
references
References 66 publications
6
252
2
5
Order By: Relevance
“…32 Newman concluded from 2 metaanalyses that African American ethnicity is a significant and independent predictor of poor outcome from breast cancer, even after accounting for SES. 33 A Southwest Oncology Group study concluded that after adjustment for SES, African American patients with breast cancer had worse adjusted survival, despite enrollment on phase 3 clinical trials with uniform stage, treatment, and follow-up. 34 Several studies have revealed disparities because of race/ethnicity, older age, and geographic location in breast cancer care, including the receipt of RT after BCS.…”
Section: Discussionmentioning
confidence: 99%
“…32 Newman concluded from 2 metaanalyses that African American ethnicity is a significant and independent predictor of poor outcome from breast cancer, even after accounting for SES. 33 A Southwest Oncology Group study concluded that after adjustment for SES, African American patients with breast cancer had worse adjusted survival, despite enrollment on phase 3 clinical trials with uniform stage, treatment, and follow-up. 34 Several studies have revealed disparities because of race/ethnicity, older age, and geographic location in breast cancer care, including the receipt of RT after BCS.…”
Section: Discussionmentioning
confidence: 99%
“…7,28,29 Other investigations have shown that equal access to medical care does not eliminate completely the survival disadvantage for African American women, [30][31][32][33] and race alone has been suggested as an independent predictor for survival. [34][35][36] African American women were noted to have significantly earlier age at diagnosis, high grade tumors, and a higher proportion of ERnegative and PR-negative cancers, 3,6,[37][38][39][40][41][42] suggesting that breast cancer is biologically different in African American women.…”
Section: Discussionmentioning
confidence: 99%
“…21,49,50 Therefore, the current study responds to calls in the literature for analyses that include these variables. 7,9,10,37,51 …”
Section: Strengths/limitationsmentioning
confidence: 99%
“…Possible explanations include differences in screening mammography leading to differences in the stage and size of tumors at diagnosis, 5,6 tumor biology, inadequate receipt of appropriate breast cancer treatment, 5 and underlying patient comorbidities and socioeconomic factors. [7][8][9][10][11] Several studies have used Surveillance, Epidemiology, and End Results (SEER) program information to explore these issues. 3,4,[12][13][14][15][16][17][18] Although SEER data include valuable regional information on a large, geographically diverse population, it lacks detailed information concerning screening mammography use and underlying comorbidities that may impact survival.…”
mentioning
confidence: 99%